PEMBANGUNAN MEDIA KONSULTASI PENYAKIT GIGI MENGGUNAKAN METODE DEMSPTER-SHAFER - Saptorini, Ernest Dwi; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2014)
Media Consulting Dental Disease Using Dempster-Shafer Method. The expert system could serve as a consultant which would advise the user as well ass the assistant for the expert. One way to prevent and help to detect persons' level of risk dental disease, by making the anexpert system as a consultant media in order that could minimize the risk of serious illness or death resulting. Diagnostic result of dental disease expert system is equal with The Dempster-Shafer inference engine. The conclusion is an expert system has been built could be applied for dental disease diagnostic.